2021
DOI: 10.3390/ijerph18052785
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Laboratory-Confirmed Bloodstream Infections—Species Diversity and Resistance Mechanisms, a Four-Year Retrospective Laboratory-Based Study in the South of Poland

Abstract: Introduction: Regardless of the country, advancements in medical care and infection prevention and control of bloodstream infections (BSIs) are an enormous burden of modern medicine. Objectives: The aim of our study was to describe the epidemiology and drug-resistance of laboratory-confirmed BSI (LC-BSIs) among adult patients of 16 hospitals in the south of Poland. Patients and methods: Data on 4218 LC-BSIs were collected between 2016–2019. The identification of the strains was performed using MALDI-TOF. Resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…[ 21 ] Chmielarczyk et al . [ 22 ] reported 279 (76.9%) from 363 patients admitted to ICU, 382 (68.6%) from 557 patients in surgical units, and 3557 (44.6%) from 7979 patients in other units had BSIs. Also, the prevalence of BSI was 17.2% in Rome, Italy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Chmielarczyk et al . [ 22 ] reported 279 (76.9%) from 363 patients admitted to ICU, 382 (68.6%) from 557 patients in surgical units, and 3557 (44.6%) from 7979 patients in other units had BSIs. Also, the prevalence of BSI was 17.2% in Rome, Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Infections by NFGNB occur in the presence of several risk factors and, predominantly, in hospitalized patients. The risk factors for infection by NFGNB, include, among other, malignancy, immunosuppression, presence of intravascular devices and drain tubes, prolonged antibiotic use, lengthy hospitalization, older age, and presence of chronic respiratory disease or of other comorbidities [41,47,48 ▪▪ ]. It is noteworthy that Elizabethkingia spp.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…For example, Chmielarczyk et al reported that M. luteus , S. aureus , E. facealis , Salmonella spp, E. coli , and C. albicans were isolated from bloodstream infections more than ten times between 2016 and 2019 in their 4‐year laboratory‐based study in the south of Poland. [ 19 ] Apart from these pathogenic microorganisms, there are also cases caused by actinobacteria, which are a wide range of Gram‐positive filamentous bacteria and also a crucial soil component.…”
Section: Introductionmentioning
confidence: 99%